Effects of Crude Oil on Aquatic Insects of Tundra Ponds - Mozley, Samuel C.; Butler, Malcolm G. (ARCTIC, 1978)
Aquatic insects are numerous and important in the ecology of tundra thaw ponds, comprising most of the biomass and production. The most common types are the caddisflies Asynarchus and Micrasema, the stonefly Nemoura, the beetle Agabus and especially larvae of the fly family Chironomidae. Studies in vitro showed no detectable mortality of these insects at doses of oil up to 1.5 l/m² Prudhoe Bay crude oil. However, field experiments on two ponds with application rates of about 10 l/m² (Pond E, 1970) and 0.24 l/m² (Pond Omega, 1975) both indicated that selective elimination of Asynarchus and Nemoura had occurred. Chironomidae in Pond Omega displayed much lower rates of adult emergence in 1976 and 1977 than in 1975, immediately before and after oil treatment, with several species in the tribe Tanytarsini most reduced. Pond E did not show low emergence rates, but the proportion of Orthocladiinae was much higher than in reference ponds. Trichotanypus was severely reduced in Pond Omega but unusually abundant in Pond E in 1976 and 1977. Effects of oil seem to be different for different species, and occur at some point during the late larval stages of insects or at metamorphosis, but toxicity experiments did not confirm this. Oil may also interfere with reproduction in insect species which remain mainly on or near the pond surface as adults. Apparent effects in field experiments are not entirely consistent with observations of Canadian researchers. Nevertheless there were several similarities and both followed patterns like those observed in marine benthic communities, such as greater effects on shore fauna, greater effects of low-molecular-weight hydrocarbons, and species-specificity of effects. There is no indication of recovery of Nemoura, Asynarchus or Tanytarsini in Pond E seven years after the spill, but biomass and abundance of the other aquatic insects remains high. We recommend that clean-up measures avoid introducing solvents or dispersants, which might be toxic to insects in the ponds